2014
DOI: 10.1902/jop.2013.120616
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preprocedural Mouth Rinsing in Reducing Aerosol Contamination Produced by Ultrasonic Scaler: A Pilot Study

Abstract: This study suggests that a routine preprocedural mouthrinse could eliminate the majority of bacterial aerosols generated by the use of an ultrasonic unit, and that 0.2% chlorhexidine gluconate is more effective than herbal mouthwash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 15 publications
1
53
0
11
Order By: Relevance
“…33 The previous studies that have evaluated the effects of different antiseptics in reducing aerosol contamination, have recommended CHX as the gold standard. 3,4,13,34,35,36 CHX as a pre-procedural rinse has been compared with other antiseptics, such as essential oils, 13 povidone iodine and ozone, 36 tea tree oil, 35 a solution containing different types of herb extracts 4 and CPC. 3 CHX was shown to be more effective than most of these other antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 The previous studies that have evaluated the effects of different antiseptics in reducing aerosol contamination, have recommended CHX as the gold standard. 3,4,13,34,35,36 CHX as a pre-procedural rinse has been compared with other antiseptics, such as essential oils, 13 povidone iodine and ozone, 36 tea tree oil, 35 a solution containing different types of herb extracts 4 and CPC. 3 CHX was shown to be more effective than most of these other antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 One limitation of the present study is that it presents results for a single dental procedure, prophylaxis with an ultrasonic scaler that has been shown to have a great potential for aerosol generation in the dental office. 1,2,3,4,5,39 However, other dental procedures can also generate a large amount of aerosol with infectious components launched into the dental environment, such as the air turbine handpiece, 6,7 air-water from a three-way syringe 8 and sodium bicarbonate jet. 39 Therefore, one could assume that rinsing with CPC would yield similar benefits if used before the majority of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] The association of these aerosols with the respiratory infections, ophthalmic and skin infections, tuberculosis, and Hepatitis B have been reported. 7 Current literature suggests that the use of an antimicrobial rinse by the patients before treatment may decrease microbial aerosols. [3][4][5] Chlorhexidine is considered as the "Gold standard" among antimicrobial rinse because of broad-spectrum antibacterial activity and high substantivity.…”
Section: Introductionmentioning
confidence: 99%
“…Preprocedural rinses with water [7] and 0.12 to 2% chlorhexine gluconate or essential oil containing mouthwashes for duration of 60 seconds can cause substantial reduction in bacterial counts [24]. A study by Gupta DG et al demonstrated the efficacy of preprocedural rinsing in chlorhexidine in reducing the aerosol contamination produced by ultrasonic scaling [38]. .1.2.…”
mentioning
confidence: 99%